GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 572 species occurrences available in GBIF matching the query: TaxonKey: Selaginella martensii Spring. The dataset includes 572 records from 43 constituent datasets: 5 records from Phanerogamic Botanical Collections (S). 4 records from University of Vienna, Institute for Botany - Herbarium WU. 40 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from SPF - Herbário da Universidade de São Paulo. 3 records from CESJ - Herbário Leopoldo Krieger. 1 records from MBM - Herbário do Museu Botânico Municipal. 1 records from Natural History Museum Maastricht (NL) - Herbarium. 1 records from iNaturalist Research-grade Observations. 3 records from CONN. 1 records from Louisiana State University Herbarium - Vascular Plants. 1 records from OAC-BIO Herbarium. 1 records from Herbario de la Universidad de Granada: GDA. 1 records from UEC - Herbário da Universidade Estadual de Campinas. 9 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 2 records from Jardin botanique de Montréal (JBM). 3 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 75 records from Tropicos Specimen Data. 1 records from Natural History Museum, Vienna - Herbarium W. 1 records from Leiner-Herbar Konstanz. 1 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 1 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 1 records from Herbario de la Universidad de Sevilla, SEV-Historico. 16 records from herbario. 1 records from Arizona State University Vascular Plant Herbarium. 1 records from UCD BOTANICAL CONSERVATORY. 1 records from MEXU/Plantas Vasculares. 1 records from MEXU/Tipos de plantas vasculares. 2 records from MEXU/Herbario Los Tuxtlas. 1 records from Herbarium Berolinense. 2 records from MEXU/Colección Histórica. 132 records from Programa de repatriación de datos de ejemplares mexicanos. 1 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 1 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 120 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Seed collection – Dead seeds for evaluation and observation purposes. 3 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 67 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 15 records from SysTax - Botanical Gardens. 15 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 2 records from Instituto de Botánica Darwinion. 14 records from Herbarium WRSL, Main Collection. 18 records from CAS Botany (BOT).
Keywords: GBIF; biodiversity; species occurrences